HOW MANY SPECIES OF ETLINGERA (ZINGIBERACEAE) ARE THERE IN THE PHILIPPINES? - POULSEN, A. D.; DOCOT, R. V. A. (Edinburgh Journal of Botany, 2018)
Based on studies of types and recent collections, the number of species of Etlingera Giseke in the Philippines is doubled from eight to 16. Three species (Etlingera alba, E. brevilabrum and E. sessilanthera) are reported here for the first time, E. pandanicarpa is synonymised with the Bornean E. fimbriobracteata, and four new combinations (E. bulusanensis, E. linearifolia, E. pubimarginata and E. subviridis) and one new name (E. pilosa) are published here. Nine lectotypifications are proposed, of which three represent second-step designations. About two-thirds of the species are currently thought to be endemic, but future fieldwork is likely to result in more species of Etlingera in the Philippines, either endemic or as new records from neighbouring islands.
Keywords: A.D.E. Elmer; Amomum; distribution; ginger; Hornstedtia; Malesia; species richness